Faktor-Faktor Yang Mempengaruhi Audit Delay Pada Kantor BPKP Di Provinsi Sumatera Utara - Santa Lusi Silalahi; Sri Ulina Barus; Ebit Mardin Hulu; Jenny Zain; Oky Syahputra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Financial reports are said to be accurate if they are presented in a timely manner when needed by users of financial statements such as the government, investors, creditors, the public, and other parties as a basis for decision making. This study aims to test and find out whether there is an effect of company size, audit opinion, auditor reputation, and audit tenure on Audit Delay. The method in this study uses quantitative methods with the sampling technique determined by the questionnaire method using the saturated sample technique, where all the population in this study is sampled. The population in this study were all auditors at the BPKP office in North Sumatra Province. the number of samples used was 62 auditors who worked at the BPKP office in North Sumatra Province. Based on the results of the research conducted, it shows that Audit Opinion and Audit Tenure have a significant effect on Audit Delay while Company Size and Audit Reputation have no significant effect on Audit Delay. Keywords: Audit Delay, Audit Tenure, Audit Opinion, Auditor Reputation, Company Size